Does Birth-Related Trauma Last? Prevalence and Risk Factors for Posttraumatic Stress in Mothers and Fathers of VLBW Preterm and Term Born Children 5 Years After Birth - Barthel, Dana; Göbel, Ariane; Barkmann, Claus; Helle, Nadine; Bindt, Carola (Frontiers in Psychiatry, 2020)
Previous research suggests that the birth of a preterm child with very low birth weight (VLBW; <1500g) can be traumatic for both parents and lead to short-term consequences like clinical levels of posttraumatic stress symptoms (PTSS) or even to the development of a Posttraumatic Stress Disorder (PTSD). However, little is known about possible mid- and long-term psychological consequences in affected parents. The purpose of this study were a) to examine the prevalence of parental birth-related PTSS and PTSD in a group of parents with VLBW preterm infants compared to parents of full-term infants five years after birth and b) to investigate potential associations with risk factors for parental PTSS at five years postpartum. Perinatal factors (VLBW preterm or term, perceived stress during birth), psychological factors (perceived social support and PTSS four to six weeks postpartum, psychiatric lifetime diagnosis) and sociodemographic characteristics (number of children, singleton or multiple birth, socio-economic status), were included in the analysis. The sample consisted of 144 families (77 VLBW, 67 term birth) who participated in the prospective longitudinal cohort study “Hamburg study of VLBW and full-term infant development” (HaFEn-study) and were initially recruited at three perinatal care centers in Hamburg, Germany. PTSD prevalence and PTSS of mothers and fathers were assessed with the Impact of Event Scale (IES-R), social support with the Questionnaire of Social Support (SOZU-K-22), and lifetime psychiatric diagnoses with the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (SCID-I). Data were analyzed by hierarchic multiple regression analyses. Results showed that five years after birth none of the parents fulfilled the criteria for a birth-related PTSD diagnosis. For mothers, postnatal PTSS and a VLBW preterm birth significantly predicted PTSS five years postpartum. For fathers, psychiatric lifetime diagnosis and postnatal PTSS significantly predicted PTSS five years after birth. Early identification of parents with higher risk of PTSS, especially after VLBW preterm birth, and their clinical needs seems beneficial to reduce the risk of long-term consequences. More research is needed on the paternal perspective and on potential effects of preterm birth on both parents and their children’s mental health outcomes.